Research as Guesthood: The Memorial to Sir Wilfrid Laurier and Resolving Indigenous-Settler Relations in British Columbia - Feltes, Emma (Anthropologica, 2015)
What happens when the subject of anthropological study intervenes in the research process itself? This paper explores a 1910 letter—dubbed the Laurier Memorial, written by the Secwépemc, Syilx and Nlaka'pamux First Nations in interior BC—which puts forward a robust vision for just political relations between Indigenous peoples and settlers, based in Indigenous law, mutual obligation, reciprocal sovereignty and shared jurisdiction. However, it turns out that the Laurier Memorial has implications for anthropological practice as well. As the Laurier Memorial helps anthropology to "find a place to stand," the resulting research relationship becomes an extension of the research content itself.